Immunogenicity and Safety of Varying Dosages of a Monovalent 2009 H1N1 Influenza Vaccine Given With and Without AS03 Adjuvant System in Healthy Adults and Older Persons - Jackson, Lisa A. (Oxford University Press, 2012)
Background. Adjuvanted vaccines have the potential to improve influenza pandemic response. AS03 adjuvant has been shown to enhance the immune response to inactivated influenza vaccines. Methods. This trial was designed to evaluate the immunogenicity and safety of an inactivated 2009 H1N1 influenza vaccine at varying dosages of hemagglutinin with and without extemporaneously mixed AS03 adjuvant system in adults ≥18 years of age. Adults were randomized to receive 2 doses of 1 of 5 vaccine formulations (3.75 µg, 7.5 µg, or 15 µg with AS03 or 7.5 µg or 15 µg without adjuvant). Results. The study population included 544 persons <65 years of age and 245 persons ≥65 years of age. Local adverse events tended to be more frequent in the adjuvanted vaccine groups, but severe reactions were uncommon. In both age groups, hemagglutination inhibition antibody geometric mean titers after dose one were higher in the adjuvanted groups, compared with the 15 µg unadjuvanted group, and this difference was statistically significant for the comparison of the 15 µg adjuvanted group with the 15 µg unadjuvanted group. Conclusions. AS03 adjuvant system improves the immune response to inactivated 2009 H1N1 influenza vaccine in both younger and older adults and is generally well tolerated. ClinicalTrials.gov NCT00963157